2005
DOI: 10.1042/bj20041389
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic Bid induces membrane perturbation by inserting selected lysolipids into the bilayer

Abstract: Bid is a BH3-only member of the Bcl-2 family that regulates cell death at the level of mitochondrial membranes. Bid appears to link the mitochondrial pathway with the death receptor-mediated pathway of cell death. It is generally assumed that the f.l. (full-length) protein becomes activated after proteolytic cleavage, especially by apical caspases like caspase 8. The cleaved protein then relocates to mitochondria and promotes membrane permeabilization, presumably by interaction with mitochondrial lipids and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 65 publications
4
33
0
Order By: Relevance
“…Bid in the mitochondrial fraction was increased by PA treatment, which was inhibited by BEL (Fig. 4C), suggesting a possible role for full-length Bid in cell death by LPC, as reported (35). Probably because of the decrease in cardiolipin content and the increase in Bid in the mitochondria, cytochrome c was translocated from mitochondria to cytoplasm and mitochondrial potential was decreased between 3 and 24 h after PA treatment (Fig.…”
Section: Roles Of Pla 2 and Lpc In Lipoapoptosissupporting
confidence: 51%
See 1 more Smart Citation
“…Bid in the mitochondrial fraction was increased by PA treatment, which was inhibited by BEL (Fig. 4C), suggesting a possible role for full-length Bid in cell death by LPC, as reported (35). Probably because of the decrease in cardiolipin content and the increase in Bid in the mitochondria, cytochrome c was translocated from mitochondria to cytoplasm and mitochondrial potential was decreased between 3 and 24 h after PA treatment (Fig.…”
Section: Roles Of Pla 2 and Lpc In Lipoapoptosissupporting
confidence: 51%
“…4B). We also studied whether LPC could directly induce changes in Bid apart from its receptor-mediated effect, because previous papers reported that Bid could perturb mitochondrial membrane in association with LPC (35). Bid in the mitochondrial fraction was increased by PA treatment, which was inhibited by BEL (Fig.…”
Section: Roles Of Pla 2 and Lpc In Lipoapoptosismentioning
confidence: 99%
“…tBid acts at mitochondria through the cardiolipin-facilitated interaction with other pro-apoptotic members of the Bcl-2 family (e.g. Bax, Bak) [28], by destabilizing mitochondrial membranes through the insertion of selected lysolipids [29] or by promoting the propagation of Ca 2+ signals to the mitochondria [30].…”
Section: Intrinsic and Extrinsic Apoptosis Pathwaysmentioning
confidence: 99%
“…Bak) to promote the formation of large homoor hetero-multimeric channels, through which IMS proteins are released [40][41][42][43]. (2) Pro-apoptotic factors may act directly on the lipidic component of the OM, or at the lipidprotein interface, thus favoring the formation of pores though which IMS proteins may exit to the cytosol [29,[44][45][46]. (3) Activated pro-apoptotic members of the Bcl-2 family may interact with components of the permeability transition pore complex (PTPC), thus favoring (or de-inhibiting) the permeability transition (PT) of the IM, that in turn leads to the physical rupture of the OM [47][48][49].…”
Section: Om Permeabilizationmentioning
confidence: 99%
“…Modifications of lipid composition and bilayer curvature of the mitochondrial membranes seem to be crucial for permeabilization. Recent work has highlighted the importance of tBid, which is able to insert into specific lysolipids of the OMM (Esposti et al, 2001;Goonesinghe et al, 2005) and to promote a negative membrane curvature of synthetic lipidic membranes (Epand et al, 2002a). These changes presumably prepare the ground for insertion and oligomerization of Bax and Bak.…”
Section: Importance Of Lipids and Membrane Topologymentioning
confidence: 99%